Stability control for testing ship refitting through ballasts - Jinghua HU (Zhongguo Jianchuan Yanjiu, 2021)
ObjectiveTo address the problem of the increased height of the center of gravity caused by the installation of testing equipment and relevant supporting construction in refitting, it is necessary to apply adequate technical measures to control the stability of the testing ship.MethodsAccording to the real ship environment, a combination of ballasting countermeasures is selected to satisfy the stability requirements, which involves using the existing ballast tanks, adding a new ballast water tank and changing a fresh water tank for ballasting, while fixed ballast is omitted. Considering that the testing ship is equipped with desalination devices, the fresh water tank capability can be reduced. As this refitting project is not permanent, a fresh water tank is selected to be filled with fresh water which is forbidden from consumption, realizing the ballasting function in a soft way. As an additional countermeasure, timely fresh water self-replenishment by the desalination devices is also suggested to prevent the stability from being reduced by over-consumption. ResultsWith the above measures applied, in normal displacement, the height of the center of gravity is reduced by 0.31 m, the metacentric height (GM) is increased by 0.25 m and the maximum wind resistance ability is increased by 9.64 m/s; in full load displacement, the height of the center of gravity is reduced by 0.27 m, the GM is increased by 0.24 m and the maximum wind resistance ability is increased by 8.89 m/s.ConclusionsThe proposed ballast method is proven effective in controlling the stability of the ship, while the flexible application of various technical approaches has certain reference significance for naval architecture projects.